A Comparative Analysis of Temperature and Humidity with PID Control System and Fuzzy Logic in Climatic Chamber (PID Control) - Rendy Dwi Sutrisno Putra (International Journal of Advanced Health Science and Technology, 2022)
A room is said to be feasible if the temperature and humidity of the room are in accordance with existing provisions. Thermohygrometer is a tool used to monitor the condition of the room. The thermoygrometer used must be traceable for its measurement results using certain media. The climatic chamber is a device that provides the desired climate regardless of the external environment. There are several systems that can be used to control temperature and humidity, one of which is the PID (Proportional Integral Differential) control system and Fuzzy Logic. This climatic chamber has been tested at temperature measuring points of 25°C, 30°C, 35°C, and humidity of 50% RH, 60% RH, 70% RH then the measurement results are compared with a calibrated thermohygrometer. The measurement results at 25°C have a response time of 7 minutes 30 seconds and an overshoot of 0.1°C, at a temperature of 30°C it has a response time of 5 minutes 15 seconds and an overshoot of 0.1°C, at a temperature of 35°C it has a response time of 5 minutes 30 seconds. and 0.2°C overshoot. At humidity 50%RH it has a response time of 13 minutes 30 seconds, at humidity 60%RH it has a response time of 12 minutes, at humidity 70%RH it has a response time of 6 minutes. The measurement results show that fuzzy logic control has more advantages than PID control. Fuzzy logic control has a faster response time to setpoint than PID control and fuzzy logic control has smaller overshoot than PID control